Enforcing obligations erga omnes in international law - Tams, Christian J. (Cambridge University Press, 2005)
The concept of obligations erga omnes - obligations to the international community as a whole - has fascinated international lawyers for decades. This book shows how this highly controversial concept has become part of modern-day international law, and how it will enhance human rights in the future.
Keywords: International obligations.; International law -- Moral and ethical aspects.; Customary law, International.; Obligations internationales.; Droit coutumier international.; POLITICAL SCIENCE -- International Relations -- Treaties.; Customary law, International; International law -- Moral and ethical aspects; International obligations